Aplikasi Sistem Pakar Mendiagnosa Penyakit Degenerasi Macula Menggunakan Metode Certainty Factor Berbasis Web - Abrar Hadi; Amalia Hanifa (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
An expert system is a system that seeks to adopt human knowledge into computers that are designed to represent the ability to solve problems like an expert. This system helps all people solve their problems or just look for quality information that can only be obtained with a dedicated expert. This study describes how the Expert System diagnoses Macular Degeneration using the Certainty Factor method. This method obtained the possible disturbances value experienced by the community. This Expert System program is implemented in the PHP programming language where MySQL as the database. As the result, this system is easy to use (user-friendly) and easy to develop and useful for those who want to know about Macular Degeneration.